RETRACTION NOTICE "ECONOMIC ANALYSIS AND FOOD SECURITY CONTRIBUTION OF SUPPLEMENTAL IRRIGATION AND FARM PONDS: EVIDENCE FROM NORTHERN BURKINA FASO" - Bétéo Zongo; Bruno Barbier; Thomas Dogot; Abdoulaye Diarra; Malicki Zorom; Calvin Atewamba; Omer S Combary; Souleymane Ouédraogo; Patrice Toé; Harouna Karambiri; Yacouba Hamma (Agricultural Socio-Economics Journal, 2022)
This article entitled â€œECONOMIC ANALYSIS AND FOOD SECURITY CONTRIBUTION OF SUPPLEMENTAL IRRIGATION AND FARM PONDS: EVIDENCE FROM NORTHERN BURKINA FASOâ€ (2022), authored by BÃ©tÃ©o Zongo, Bruno Barbier, Thomas Dogot, Abdoulaye Diarra, Malicki Zorom, Calvin Atewamba, Omer S Combary, Souleymane OuÃ©draogo, Patrice ToÃ©, Harouna Karambiri, Yacouba Hamma, published in Volume 22, Issue 1. of Agricultural Socio-Economics Journal (AGRISE), pp. 59-75 has been retracted as requested by the authors.